2022
DOI: 10.3390/coatings12111739
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the Electrochemical Performance of Strontium (Sr)-Doped LaMnO3 as Supercapacitor Materials

Abstract: In this study, Strontium (Sr)-doped perovskite lanthanum manganite (La1−xSrxMnO3) nanoparticles were prepared by the sol–gel method and used as electrode materials of supercapacitors. Microstructures, morphologies, and electrochemical properties of the samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), a transmission electron microscope (TEM), Brunauer–Emmett–Teller (BET) surface area measurements, cyclic voltammetry (CV), and galvanostatic charge/discharge (GCD) cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Doping causes a reduction in the average ionic radius at point A due to the larger ionic radius of La 3+ (1.06 Å) compared to Ca 2+ (0.99 Å). The presence of alternating long and short A-site cation radii can lead to a significant mismatch in the MnO 6 octahedra and a pronounced bending of the Mn-O-Mn bond angles [21,22,29]. This mismatch exerts a considerable influence on the orthorhombic structure, causing elongation along the c-axis due to the Jahn-Teller effect and amplifying the lattice distortion of the compounds [21,22,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doping causes a reduction in the average ionic radius at point A due to the larger ionic radius of La 3+ (1.06 Å) compared to Ca 2+ (0.99 Å). The presence of alternating long and short A-site cation radii can lead to a significant mismatch in the MnO 6 octahedra and a pronounced bending of the Mn-O-Mn bond angles [21,22,29]. This mismatch exerts a considerable influence on the orthorhombic structure, causing elongation along the c-axis due to the Jahn-Teller effect and amplifying the lattice distortion of the compounds [21,22,29].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of alternating long and short A-site cation radii can lead to a significant mismatch in the MnO 6 octahedra and a pronounced bending of the Mn-O-Mn bond angles [21,22,29]. This mismatch exerts a considerable influence on the orthorhombic structure, causing elongation along the c-axis due to the Jahn-Teller effect and amplifying the lattice distortion of the compounds [21,22,29]. It is clear that replacing La 3+ with a smaller Ca 2+ reduces the lattice volume and thus increases the diffraction angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that La 2 NiO 4 is a p-type conductor. 27 If charge compensation occurs according to eqn (6), doping of Sr will generate more charge carriers, and hence conductivity will increase. On the other hand, a decrease in the activation energy with increasing Sr content is possible due to an increase in the number of hopping sites.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…To address these limitations, researchers have shifted their focus toward exploring negative permittivity in homogeneous or single-phase materials. Negative permittivity has been reported in various single-phase materials: Sr-doped LaMnO 3 , [6][7][8] Mn-doped Sr 2 SnO 4 , 9 Nbdoped Sr 2 MnO 4 , 10 Sb-doped SnO 2 , 11 and Sn-doped In 2 O 3 . 12 We have put continuous efforts into exploring single-phase materials to achieve negative permittivity at room temperature in pristine (undoped) compounds.…”
Section: Introductionmentioning
confidence: 99%